HEALTH DISPARITIES, SOCIAL DETERMINANTS OF HEALTH, AND SYSTEMIC ANTI-BLACK RACISM DURING COVID-19: A CALL TO ACTION FOR SOCIAL WORK - Massaquoi, Notisha; Ashcroft, Rachelle; Adamson, Keith (Canadian Social Work Review / Revue canadienne de service social)

(untitled) (Canadian Association for Social Work Education / Association canadienne pour la formation en travail social (CASWE-ACFTS), 2022)
Systemic anti-Black racism is deeply rooted in the social, political, economic, ontological, and epistemological foundations of Canadian society. Driven by our code of ethics and the most recent call to reckon with anti-Black racism in society, the social work profession’s advocacy agenda requires reconceptualization to eradicate anti-Black racism and the creation of equitable environments within which Black communities can thrive. This article examines the anti-Black racism exhibited during the COVID-19 pandemic through the lens of health equity and health disparity. The interplay between health disparities, social determinants of health, and systemic anti-Black racism is highlighted and the urgency for social workers to respond to the causes of poor Black health outcomes is emphasized. Social workers are called upon to engage in a more intentional framework of Black health equity, which includes a practice that ensures the well-being and survival of Black people and their communities. The authors conclude that for the social work profession to reach its full potential, it must recognize and use its distinctive qualities to eradicate anti-Black racism.